2021
DOI: 10.3393/ac.2021.00836.0119
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Intersphincteric Resection for Low Rectal Cancer: Technical Controversies and a Systematic Review on the Perioperative, Oncological, and Functional Outcomes

Abstract: Intersphincteric resection (ISR) is the ultimate anus-sparing technique for low rectal cancer and is considered an oncologically safe alternative to abdominoperineal resection. The application of the robotic approach to ISR (RISR) has been described by few specialized surgical teams with several differences regarding approach and technique. This review aims to discuss the technical aspects of RISR by evaluating point by point each surgical controversy. Moreover, a systematic review was performed to report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…Obviously, this is influenced by not subdividing the early rectal cancer to very early (T1 without poor prognostic factors, where local excision is sufficient). Selection by the respondents of organ-preserving and minimally invasive conservative treatment was possibly related to the fact that radical surgery is associated with a high percentage of postsurgical complications (3%-30% [33]) and organ dysfunction (defecation disorder up to 75%-90%, sexual dysfunction up to 50%, and urination dysfunction up to 30% [13,[34][35][36][37][38][39][40]). Moreover, bowel dysfunction is a long-lasting issue [14].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this is influenced by not subdividing the early rectal cancer to very early (T1 without poor prognostic factors, where local excision is sufficient). Selection by the respondents of organ-preserving and minimally invasive conservative treatment was possibly related to the fact that radical surgery is associated with a high percentage of postsurgical complications (3%-30% [33]) and organ dysfunction (defecation disorder up to 75%-90%, sexual dysfunction up to 50%, and urination dysfunction up to 30% [13,[34][35][36][37][38][39][40]). Moreover, bowel dysfunction is a long-lasting issue [14].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Several studies have described technical issues of robotic ISR and shown acceptable perioperative, oncological, and functional outcomes of robotic ISR for low-lying rectal cancer patients [ 57 58 ]. However, there is a risk of worse anorectal functional outcomes, which can threaten the quality of life in some patients including those with very-low rectal cancer and those who have received radiotherapy.…”
Section: Extended Techniques In Robotic Surgerymentioning
confidence: 99%
“…The data that support the findings of this study are openly available in [repository name e.g "figshare"] at http://doi. org/10.1002/ccr3.6356, reference number [ 9 ].…”
Section: Author Contributionsmentioning
confidence: 99%